Dynamics of Graft Function Measured by DNA-Technology in a Patient with Severe Aplastic Anemia and Repeated Stem Cell Transplantation - Anna Karastaneva; Christian Urban; Herwig Lackner; Wolfgang Schwinger (Case Reports in Medicine)
Although bone marrow transplantation (BMT) from an HLA identical sibling is considered as treatment of choice in pediatric patients with severe aplastic anemia (SAA), a significant number of them experience graft failure (GF) after BMT. We report a case of an 8-year-old male patient with SAA who presented with a complicated posttransplant course due to parvovirus B19 infection and GF. A subsequent attempt to support the graft by antithymocyte globulin (ATG) and a peripheral stem cell boost resulted in transitory autologous recovery of hematopoiesis followed by mixed chimerism, supported by donor lymphocyte infusions (DLIs) and finally graft rejection with relapse of SAA. Permanent complete chimerism was achieved by a second BMT. Dynamics of graft function, measured by a single nucleotide polymorphism (SNPs) analysis, are discussed.